NEUROMYELITIS OPTICA SPECTRUM DISORDERS: THERAPEUTIC CONSIDERATIONS: NMOSD therapeutic considerations - Andabaka, Marko; Mesaroš, Šarlota; Veselinović, Nikola; Tamaš, Olivera; Budimkić, Maja; Drulovic, Prof. Jelena (Medical Research, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare but debilitating autoimmune disease of the central nervous system (CNS) for which several biological therapies have recently been approved. Historically, NMOSD disease-modifying treatments relied on wide-spectrum off-label conventioanl immunosuppressants, such as azathioprine, and mycophenolate mofetil. Since 2015, evidence has accumulated to support off-label biological therapy (rituximab) and to approve satralizumab, inebilizumab, eculizumab, and ravulizumab. This next generation of drugs provides several targeted disease-modifying treatment options for NMOSD. Here, we first review the mechanistic rationales associated with their specific targets. We then review the pivotal evidence supporting their use in practice. The current therapeutic options in NMOSD comprise three targeted mechanisms at different stages of a unique tissue-injury cascade: B-cell depleting, anti-cytokine, and anti-complement therapies. One drug has been approved on the market in each class. The current consensus proposes positioning the approved drugs as first-line treatments for newly-diagnosed patients and as alternative therapies in case of failure of historical treatment.
Keywords: Neuromyelitis optica spectrum disorder, treatment, disease-modifying treatment